Halal Tourism Power: Analysis the Effect of Perceptions and Interests on Tourist Attitudes in Visiting Halal Tourism - Rizki, Mochamad; Wiranatakusuma, Dimas Bagus (Universitas Muhammadiyah Yogyakarta, 2020)
Halal issue is the impotant part in Islam. In the past few decades, halal industries have undergone evolution as the Islamic economy developed in the world and one of them is in the tourism sector, namely halal tourism as a means of building awareness of the economic potential, culture and noble Islamic civilization. The existence of tourism is very closely related to sustainable development goals. The existence of tourism will help both directly and indirectly in achieving the SDGs. Well-managed tourism will affect the following targets: eradication of poverty and hunger, capital for the development of better public health, the emergence of innovation and supporting industries, spur more responsible consumption and production. Of course this attracts a lot of attention from tourists to visit this sharia tourism. If we seen in economics standpoint, tourism certainly has a very high influence on economic growth because tourism itself is part of the development sector that can spur economic growth. Therefore, this study aims to investigate the effect of perceptions and interest of halal tourism on tourist attitudes in visiting halal tourism. This paper uses quantitative approach. This study used primary data by a paper-based survey in the Google form. The data were analyzed using IBM SPSS Statistics 20. The data analysis model used in this study is a Multiple Regression analysis and the data will analized using explanatory descriptive analysis methods. The result from this research we can conclude that the consumer is undestand about halal tourism and consumer interest in halal tourism so it can influence to attitudes consumer to vistiting halal tourism in future.